A57Fe Mössbauer study of rust coonverters - Bolívar, Francisco; Ríos, John; Barrero, César; Minotas, Julio; Morales, Álvaro; Arroyave, Carlos (Revista Facultad de Ingeniería Universidad de Antioquia, 2003)
Rust converters are substances used to prepare corroded surfaces in structures, with the purpose to transform the rust oxides or hydroxides to more stable products, thus constraining their participation in further corrosion processes and allowing the application of paint schemes. In this work, results obtained from two different experimental works, which evaluated different converter formulations and type of corroded surface are presented and compared. Sorne of the experimental conditions were similar in both works, i. e., AISI SAE 1008 carbon steels were used, and the samples were pretreated to obtain a certain degree of oxidation using the same standard method by immersiondrying conditions. However, in the first work, the formulations used different concentration in tanic and phosphoric acids as the independent variable and pure isopropilic alcohol, pure terbutilic alcohol and a mixture of them were used as solvents; whereas in the second work, phospboric acid content was maintained constant and variations in tannic acid and as solvents mixtures of isopropilic and terbutilic alcohol were used. Converters were applied over the samples, some of these previously grinded (the superficial rust layer thus eliminated) and others without grinding, before painting and exposed to tests in accelerated corrosion chambers. The transformation of the rust was monitored by Mössbauer 57Fe spectroscopy, both at room temperature and at 77 K. It was found that each content in tannic acid has a mixture of alcohols that improved the rust conversion.